MSME HUMAN CAPITAL TO BUILD SUSTAINABLE MSMES IN THE INDUSTRY ERA 5.0 (CASE STUDY OF MSMES IN KLOJEN MARKET) - Muhammad Dzulfahmi Mubarok; Rifdah Abadiyah (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: As the Industry 5.0 era develops, MSMEs must concentrate on developing human resources as the primary driver of company in addition to using technology. In order to support MSMEs' aspirations in the era of Industry 5.0, this study will examine the human capital model of MSME actors in Klojen Market, Malang City. Method: The study employs a qualitative descriptive methodology, gathering data through documentation, interviews, and observation. MSME actors, market managers, and academics who were purposefully chosen served as research informants. The stages of data reduction, data presentation, and conclusion drawing were used in the data analysis process, together with source and technique triangulation for data validity assessment. Results: The study findings show that the four main indicators of human capital of MSMEs in Klojen Market are experience, expertise, behavior, and skills. Building MSME flexibility and resilience to market shifts and crises begins with business experience. Improving transaction efficiency and company competitiveness is influenced by expertise and skills, especially digital skills such as the use of social media and QRIS. Maintaining social connections with clients and acting in a friendly and communicative manner are examples of human-centricity, which is consistent with the characteristics of Industry 5.0. Furthermore, human capital drives sustainability and resilience through business hygiene, environmental awareness, and adaptability. Novelty: According to the study findings, the sustainability of MSMEs in the Industry 5.0 era is highly dependent on the quality of their human capital.